A Case Report of Successful Cataract Surgery in Theil-Behnke Corneal Dystrophy: A Visual Rehabilitation for the Patient - Radhika Paranjpe; Varsha Manade; Preethi Abraham; Khushboo Goyal; Surbhi Chodvadiya (Case Reports in Ophthalmology)
Introduction: Thiel-Behnke corneal dystrophy is a rare inherited condition characterized by symmetrical subepithelial corneal opacities that gradually reduce vision. It is an autosomal dominant inherited epithelial stromal TGFB1 dystrophy that mainly causes visual impairment. Case Presentation: This case report describes case of a woman in her early 50s with progressive vision loss in her left eye over the past 3 months with a history of recurrent corneal erosions in childhood. Examination on a slit lamp showed corneal dystrophy affecting both eyes, matching the features of Thiel-Behnke dystrophy. Diagnosis was confirmed with anterior segment-optical coherence tomography, revealing a distinctive sawtooth pattern in Bowman’s layer. The patient was managed conservatively for her dystrophy and was also surgically treated for her cataract in the left eye, which showed a significant improvement in her vision. Conclusion: Despite its rarity, Thiel-Behnke dystrophy along with cataract can severely impair vision, making early diagnosis and continuous monitoring crucial for preventing further visual decline.